Should China access to the convention on the protection of underwater cultural heritage? — A SWOT analysis - Yuan, Wei (Frontiers in Marine Science, 2022)
In recent years, with China’s marine strength having enhanced, the discussion on whether to access to the ‘Convention on the Protection of Underwater Cultural Heritage’ has become increasingly prominent. A growing number of experts and scholars believe that the current domestic laws cannot meet the needs of development; thus accession to the ‘Convention’ may after all be accepted as a solution. Given the current development in China, it cannot be generalized whether it is appropriate to access to the ‘Convention’. Indeed, based on the analysis of comparison between status quo of domestic legislation and international marine development, there is no necessity for China to eagerly access to the ‘Convention’, in that for many issues, the domestic laws in China have many differences with international law, and still need further development and improvement.